Transmedia influence on Covid-19 television coverage in Brazil: a case study to broaden the debate - Faria, Cristiano Eduardo (2021)
The use of transmedia storytelling narrative in journalism, in addition to corresponding to a business model driven by the convergence in contemporary media, can be considered the way for the public to immerse themselves in the informative universe. In times of Covid-19 pandemic, TV news coverage in Brazil reinforces that journalism should not be just declaratory, being insufficient to invest only in statistics and report scientific studies around the world. Thus, the transmedia storytelling narrative emerges as a proposal capable of enabling the public to immerse themselves in this new pandemic reality. This article seeks to reflect on the use of transmedia narrative in television journalism, through the analysis of the reports of the program Fantástico, from Rede Globo, in the first month of coverage of Covid-19 in Brazil, between 03/15/2020 to 04/05/2020. It is also intended to dissociate the use of this narrative in journalism and fiction in order to broaden the recognition of its application in television news, in addition to pointing out the changes in the performance of reporters and interviewees in narrative construction in times of pandemic.